Peningkatan Kosakata Bahasa Jerman Melalui Penggunaan Media Cerita Pendek - Anding, Maria Februona; Saud, Syukur; Rijal, Syamsu (Interference: Journal of Language, Literature, and Linguistics, 2021)
Abstract. This study aims to determine the increase in German vocabulary mastery. students in class XII Hotel Accommodation at SMK Santa Theresa Nangalili, West Manggarai Regency through short story media. This type of research is the Classroom Action Research model of Kemmis and Mc Taggart. The subjects in this research were students of class XII Hotel Accommodation, which amount to 30 people. This research was conducted in two cycles, which cycle I and cycle II, and each cycle consisted of four stages, that’s planning, implementing, observing, and reflecting. From the results of the German vocabulary mastery test, students obtained an average score of 64.93 in the first cycle and an increase in the second cycle with an average score of 80,67. The results of this research indicate that the use of short story media in learning can improve German vocabulary, as well as positive attitudes and activeness of students class XII Hotel Accommodation at SMK Santa Theresa Nangalili, West Manggarai- Nusa Tenggara Timur Regency.